Correction to: Comparative effectiveness and safety of non-vitamin K antagonists for atrial fibrillation in clinical practice: GLORIA-AF Registry. - Lip, Gregory Y. H.; Kotalczyk, Agnieszka; Teutsch, Christine; Diener, Hans-Christoph; Dubner, Sergio J.; Halperin, Jonathan L.; Ma, Chang-Sheng; Rothman, Kenneth J.; Marler, Sabrina; Gurusamy, Venkatesh Kumar; Huisman, Menno V. (Clinical Research in Cardiology, 2022)
In this article, the name of the GLORIA-AF investigator Anastasios Kollias was given incorrectly as Athanasios Kollias in the Acknowledgements. The original article has been corrected.
EVALuna2:522842